2015
DOI: 10.1186/s12866-015-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxygen consumption in Herbaspirillum seropedicae fnr mutants leads to increased NifA mediated transcriptional activation

Abstract: BackgroundOrthologous proteins of the Crp/Fnr family have been previously implicated in controlling expression and/or activity of the NifA transcriptional activator in some diazotrophs. This study aimed to address the role of three Fnr-like proteins from H. seropedicae SmR1 in controlling NifA activity and consequent NifA-mediated transcription activation.ResultsThe activity of NifA-dependent transcriptional fusions (nifA::lacZ and nifB::lacZ) was analysed in a series of H. seropedicae fnr deletion mutant back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
4
2
Order By: Relevance
“…We do not know whether Fnr5 or Fnr7 could bind to the promoter region of glnR. In contrast to our results, the combined deletions in both the fnr1 and fnr3 genes in H. seropedicae led to higher expression of nifA , nifB and nifH , which was probably as a consequence of their influence on respiratory activity in relation to oxygen availability (16). It was shown that Fnr was required for relief of NifL inhibition in K. oxytoca under anaerobic conditions (14).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We do not know whether Fnr5 or Fnr7 could bind to the promoter region of glnR. In contrast to our results, the combined deletions in both the fnr1 and fnr3 genes in H. seropedicae led to higher expression of nifA , nifB and nifH , which was probably as a consequence of their influence on respiratory activity in relation to oxygen availability (16). It was shown that Fnr was required for relief of NifL inhibition in K. oxytoca under anaerobic conditions (14).…”
Section: Discussioncontrasting
confidence: 99%
“…Fnr-related transcriptional regulators of the Crp/Fnr (cyclic AMP-binding protein/fumarate nitrate reduction regulatory protein) family have been reported to be involved in nitrogen fixation of some Gram-negative diazotrophs (1215). For example, Fnr proteins are indirectly involved in controlling the activity of NifA in Herbaspirillum seropedicae SmR1 by regulating respiratory activity in relation to oxygen availability (16, 17). Fnr protein of Klebsiella oxytoca is required to relieve inhibition of NifA activity by its partner regulatory protein NifL under anaerobic conditions (14).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the quadruple deletion mutation of fnr1, fnr3, fnr5, and fnr7 resulted in the lowest growth rates among all fnr deletion mutants and near loss of the nitrogenase activity and nifH transcript. It was reported previously that there are three fnr-like genes and that Fnr1 and Fnr3 were indirectly involved in controlling the activity of NifA in H. seropedicae (16). Fnr1 and Fnr3 of H. seropedicae directly regulate discrete groups of promoters (groups I and II, respectively), while Fnr3-Fnr1 heterodimers regulate a third group (group III) promoters (23).…”
Section: Figmentioning
confidence: 94%
“…Fnr-related transcriptional regulators of the Crp/Fnr (cyclic AMPbinding protein/fumarate nitrate reduction regulatory protein) family have been reported to be involved in nitrogen fixation of some Gram-negative diazotrophs (12)(13)(14)(15). For example, Fnr proteins are indirectly involved in controlling the activity of NifA in Herbaspirillum seropedicae SmR1 by regulating respiratory activity in relation to oxygen availability (16,17). The Fnr protein of Klebsiella oxytoca is required to relieve inhibition of NifA activity by its partner regulatory protein NifL under anaerobic conditions (14).…”
mentioning
confidence: 99%
“…β-Galactosidase assays were performed as described previously ( 11 , 29 , 30 ). To reach oxygen limiting conditions for assays using the E. coli BTH101 (bacterial two hybrid reporter) strain, we used 6 ml screw cap bijou universals filled to the top with LB medium supplemented with 1% glucose as described elsewhere ( 31 ).…”
Section: Methodsmentioning
confidence: 99%